Impact in granular matter: Force at the base of a container made with one movable wall - Torres Cisneros, Luis Armando; Marzulli, Valentina; Windows-Yule, C. R. K.; Pöschel, Thorsten (Physical Review E, 2020)
In geotechnics as well as in planetary science, it is important to find a means by which to protect a base from impacts of micrometeoroids. In the moon, for example, covering a moon base with regolith, and housing such regolith by movable bounding walls, could work as a stress-leaking shield. Using a numerical model, by performing impacts on a granular material housed in a rectangular container made with one movable sidewall, it is found that such wall mobility serves as a good means for controlling the maximum force exerted at the container's base. We show that the force exerted at the container's base decreases as the movable wall decreases in mass, and it follows a Janssen-like trend. Moreover, by making use of a dynamically defined redirecting coefficient K (X), proposed by Windows-Yule et al. [Phys. Rev. E 100 , 022902 (2019)], which depends on the container's width X , we propose a model for predicting the maxima measured at the container's base. The model depends on the projectile and granulate properties, and the container's geometry.
CRIS-Team WoS Importer:2020-07-31